Genetic inactivation of European sea bass (Dicentrarchus labrax L.) eggs using UV-irradiation: observations and perspectives. - Julie Colléter; David J Penman; Stéphane Lallement; Christian Fauvel; Tanja Hanebrekke; Renate D Osvik; Hans C Eilertsen; Helena D'Cotta; Béatrice Chatain; Stefano Peruzzi (PLoS ONE)
Androgenesis is a form of uniparental reproduction leading to progenies inheriting only the paternal set of chromosomes. It has been achieved with variable success in a number of freshwater species and can be attained by artificial fertilization of genetically inactivated eggs following exposure to gamma (γ), X-ray or UV irradiation (haploid androgenesis) and by restoration of diploidy by suppression of mitosis using a pressure or thermal shock. The conditions for the genetic inactivation of the maternal genome in the European sea bass (Dicentrarchus labrax L.) were explored using different combinations of UV irradiation levels and durations. UV treatments significantly affected embryo survival and generated a wide range of developmental abnormalities. Despite the wide range of UV doses tested (from 7.2 to 720 mJ x cm(-2)), only one dose (60 mJ x cm(-2) x min(-1) with 1 min irradiation) resulted in a small percentage (14%) of haploid larvae at hatching in the initial trials as verified by flow cytometry. Microsatellite marker analyses of three further batches of larvae produced by using this UV treatment showed a majority of larvae with variable levels of paternal and maternal contributions and only one larva displaying pure paternal inheritance. The results are discussed also in the context of an assessment of the UV-absorbance characteristics of egg extracts in this species that revealed the presence of gadusol, a compound structurally related to mycosporine-like amino acids (MAAs) with known UV-screening properties.